EDUCATION DURING THE ERA OF ECONOMY OF KNOWLEDGE - N. A. Suvorov (Научный вестник МГТУ ГА)
Features of modern economy as "economy of knowledge" are defined. The changes happening in education in the conditions of strengthening of a role of knowledge in economic life of society are considered. Tasks of modern universities in production of knowledge are characterized, connection of the state, universities and business is shown. The main directions of development of modern education in the conditions of emergence of new educational technologies and pressure of market forces are proved. Proposals of rectors of higher education institutions about revival of engineering education in the Russian Federation are systematized.